Engaging Parents to Promote Children's Nutrition and Health: Providers' Barriers and Strategies in Head Start and Child Care Centers. Issue 2 (March 2017) - Dev, Dipti A.; Byrd-Williams, Courtney; Ramsay, Samantha; McBride, Brent; Srivastava, Deepa; Murriel, Ashleigh; Arcan, Chrisa; Adachi-Mejia, Anna M.
Purpose: Using the Academy of Nutrition and Dietetics benchmarks as a framework, this study examined childcare providers' (Head Start [HS], Child and Adult Care Food Program [CACFP] funded, and non-CACFP) perspectives regarding communicating with parents about nutrition to promote children's health. Design: Qualitative. Setting: State-licensed center-based childcare programs. Participants: Full-time childcare providers (n = 18) caring for children 2 to 5 years old from varying childcare contexts (HS, CACFP funded, and non-CACFP), race, education, and years of experience. Methods: In-person interviews using semi-structured interview protocol until saturation were achieved. Thematic analysis was conducted. Results: Two overarching themes were barriers and strategies to communicate with parents about children's nutrition. Barriers to communication included—(a) parents are too busy to talk with providers, (b) parents offer unhealthy foods, (c) parents prioritize talking about child food issues over nutrition, (d) providers are unsure of how to communicate about nutrition without offending parents, and (e) providers are concerned if parents are receptive to nutrition education materials. Strategies for communication included—(a) recognize the benefits of communicating with parents about nutrition to support child health, (b) build a partnership with parents through education, (c) leverage policy (federal and state) to communicate positively and avoid conflict, (d) implement center-level practices to reinforce policy, and (e) foster a respectful relationship between providers and parents. Conclusion: Policy and environmental changes were recommended for fostering a respectful relationship and building a bridge between providers and parents to improve communication about children's nutrition and health.